Diseño estructural optimizado de un edificio de concreto armado - Aguila Salas, Wender Del (2000)
The present work aims the analysis and design of a six-story building of reinforced concrete under the philosophy to obtain a structure with maximum safety and minimum cost. For this has been proposed three types of structures to select one whose answer has simultaneously increased strength, stiffness and economy. The structure has idealized as a three-dimensional gantry with plates. All flooring systems were modeled as diaphragms rigid taking three degrees of freedom per level. The analysis was made with the help of the programs of computer SAP90 and ETABS. It was taken as a basis of comparison to the aporticado(columnas y vigas) system, and then with the fmalidad increase rigidity, plates were added to form a dual system that provides higher strength and lower cost. He easo of the block 1 the structuring more optima turned out to be the third by have less spin and lower displacement and, for the case of the block 11, the structuring more opt...